Virtual Care Centers and the Evolving Role of Nurses - Sonneveld, Henk; Tan, Apphia; Leenen, Jobbe P.L.; van Houwelingen, Thijs (38th Bled eConference: Empowering Transformation: Shaping Digital Futures for All: Conference Proceedings, 2025)
New Virtual Care Centers (VCCs) within hospitals utilize information technology to remotely monitor and support patients with chronic diseases living at home. Nurses play a crucial role by providing remote coaching and guidance to help patients manage their conditions. Currently, there is a growing understanding regarding the evolving roles and responsibilities of nurses in VCCs, however studies have yet to establish connections with educational frameworks, which poses a challenge for nursing education programs to prepare students for this emerging professional role effectively. Our study aimed to provide insights into the evolving roles, tasks, and responsibilities of nurses providing remote care as per the CanMEDS framework. We conducted a qualitative content analysis of 15 interviews. Nursing work within VCCs is represented by the seven CanMEDS roles. Most tasks align with the roles of Leader and Collaborator, while Quality Promotor has the fewest. Our study maps the responsibilities and tasks of VCCs' care delivery to the core roles of nurses.